Tackling antimicrobial resistance: developing and implementing antimicrobial stewardship interventions in four African commonwealth countries through a health partnership model - Diane Ashiru-Oredope; Maxencia Nabiryo; Lisa Zengeni; Nduta Kamere; Alexia Makotose; Omotayo Olaoye; William Townsend; Beatrice Waddingham; Ayodeji Matuluko; Winnie Nambatya; Yvonne Esseku; Ama Bartimeus; et al. (AOSIS, 2023)
In recent years, health partnerships have shared infection prevention and control innovations between United Kingdom hospitals and Low-Middle-Income Countries. However, none had focused on antimicrobial stewardship (AMS), a core component of tackling antimicrobial resistance (AMR). This paper documents an effective approach to developing a program to increase AMS capacity in four African countries: Ghana, Tanzania, Uganda, and Zambia as part of the Commonwealth Partnerships for Antimicrobial Stewardship (CwPAMS) program. A systematic approach was applied to assess gaps in AMS interventions and inform the development of the CwPAMS program through deskbased assessments, including National Action Plans on AMR, online focus group meetings, and expert advisory group reviews. Twelve partnerships were selected for the CwPAMS program. AMS support tools were developed based on recommendations from the scoping, including an AMS checklist tool, a healthcare worker knowledge and attitudes questionnaire, and an antimicrobial prescribing app to support clinical decision-making. Training workshops on AMS were developed and delivered to volunteers in Africa and the UK using a train-the-trainer model. The tools and workshops facilitated capacity building for AMS through the generation and strengthening of knowledge, skills, commitment, structures, systems, and leadership among stakeholders in the UK and Africa. The overall average rating assigned to the program following independent evaluation using the Organisation for Economic Cooperation and Development Assistance Committee Evaluation Criteria was very good. The evaluation also highlighted that the majority of the HPs (75%) focused on AMS and/or improved prescribing practice; all HPs have developed and implemented AMS strategies, guidelines, and tools within their hospitals; and NHS staff were able to translate the knowledge and skills they had received early on in the program into clinical practice in response to COVID-19 challenges./p